An economic and social review of the preferred bidders under the small projects IPP procurement programme: a cross-case synthesis - Mew, Timothy (Department of Mechanical Engineering, 2020)
The literature on the economic and social impacts of infrastructure projects, such as renewable energy projects, largely point towards these projects having positive direct and indirect benefits for the local economy, especially if the ownership, components, construction, and operation are sourced from local enterprises. The recipients of project expenditure, the location of their employees and to whom the profits accrue are essentially the factors that determine how much local economic benefit these renewable energy projects have. With this in mind, the Renewable Energy Independent Power Producers Procurement Programme (REIPPPP) was structured in such a way that gave additional weighting to socioeconomic criteria such as job creation, local content, local ownership, Socioeconomic Development (SED) funding, and Enterprise Development (ED) funding among others. The structuring of the REIPPPP in this way highlights the overarching policy objectives in the energy sector and how these renewable energy projects have been identified by the government as a means to achieve these socioeconomic objectives. The REIPPPP formed the foundation upon which the Small Projects Independent Power Producers Procurement Programme (SP-IPPPP) was based. The SP-IPPPP was created by the government to further localise the renewable energy industry in South Africa and give local developers and suppliers better access into this emerging sector. This research sought to compare Small Projects under the SP-IPPPP with projects of the same technology under the REIPPPP (in bid window 3 and 4) in a cross-case synthesis. Using an embedded, multiple-case study design the commitments made by Preferred Bidders in each programme were compiled and contrasted. Following this, the results for the Small Projects were scaled-up to identify how justified the additional costs associated with the Small Projects are, given their co-benefits to the South African economy. The findings suggest that the impact of the Small Projects on the overall price of renewable energy from the chosen cases would be negligible; and therefore, the co-benefits from these projects could justify this price premium. Even when scaled-up to the 400 MW allocated to Small Projects, the impact on the overall cost of renewables from BW3 and BW4 could be argued to have been justified by the co-benefits afforded by these Small Projects. The impact on the electricity price from projects in the scenario and BW3 and BW4 was not substantial; however, the job creation, local (national) expenditure, and community (within 50km of the project site) benefit were substantial, which may vi incentivise policy makers to go ahead with the procurement in order to meet these soci oeconomic objectives. In terms of the best technology option for the SP-IPPPP, the findings suggest that solar PV and biomass (in particular) are better suited to this capacity and offer improved socioeconomic benefits without a drastic price premium. Wind energy on the other hand, appeared to have a notable price premium over the Large Projects without proportionate socioeconomic benefits and would perhaps be better left to the REIPPPP.